Aggression and prosocial behaviors in social conflicts mediating the influence of cold social intelligence and affective empathy on children's social preference. Issue 4 (25th April 2014) - Carreras, M. R.; Braza, P.; Muñoz, J. M.; Braza, F.; Azurmendi, A.; Pascual‐Sagastizabal, E.; Cardas, J.; Sánchez‐Martín, J. R.
<x xml:space="preserve">Abstract</x> This study proposes a model in which aggressive and prosocial behaviors exhibited in social conflicts mediate the influence of empathy and social intelligence to children's social preference by same‐sex peers. Data were obtained from kindergarten to the end of the first grade. The sample yielded 117 Spanish children (64 girls and 53 boys) with a mean age of 62.8 months (SD = 3.3) at the beginning of the study. For boys, affective empathy contributed to boys' social preference through a decrease in physical aggression as responses to social conflict. For girls, affective empathy had an indirect effect on girls' preference by increasing assistance to others in their conflicts. No mediating effect in the contribution of social intelligence on girls' social preference was detected. Our results suggest that, only for girls, cold social intelligence can promote both indirect aggression (coercive strategic that do not leave social preference, at least at these ages) and behaviors that lead social preference (such as prosocial behaviors).